Soviet naval developments : . capability and context . papers relating to Russia's maritime interests - edited by Michael MccGwire. (Praeger, 1973)
Based on the 1972 Seminar on Soviet Naval Developments. "Published for the Centre for Foreign Policy Studies, Department of Political Science, Dalhousie University, Halifax, N. S."